1985
DOI: 10.1097/00000658-198511000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Splenic Preservation and Their Effect on Clearance of Pneumococcal Bacteremia

Abstract: The intravascular clearance of type 3 Streptococcus pneumoniae was studied in Sprague-Dawley rats. Sham celiotomy was performed on 20 animals while another 20 rats underwent splenectomy. Four weeks later, bacteremia was induced by intraperitoneal (IP) injection of S. pneumoniae. Serial cultures of peripheral blood were obtained. Splenectomy produced significant impairment of intravascular clearance of bacteria compared to that noted among control animals (p less than 0.01). Eighty animals were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…During infections, the sequestration of bacteria induces the synthesis of antibodies in subjects with a preserved spleen. After total splenectomy (TS), the levels of IgG and IgA vary widely and may be normal or elevated, but most of the available data suggest a reduction of IgM [3,7–10]. Furthermore, in patients undergoing TS, the levels of CD4 + T lymphocytes (helper), the proportion of CD4 + /T CD8 + T lymphocytes (helper/suppressor) and the competence of T lymphocytes themselves, in general, is reduced, which may be due to the minimization of the mitogenic responsive capacity of these cells [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During infections, the sequestration of bacteria induces the synthesis of antibodies in subjects with a preserved spleen. After total splenectomy (TS), the levels of IgG and IgA vary widely and may be normal or elevated, but most of the available data suggest a reduction of IgM [3,7–10]. Furthermore, in patients undergoing TS, the levels of CD4 + T lymphocytes (helper), the proportion of CD4 + /T CD8 + T lymphocytes (helper/suppressor) and the competence of T lymphocytes themselves, in general, is reduced, which may be due to the minimization of the mitogenic responsive capacity of these cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental investigations have shown that, after a certain period, autotransplanted splenic tissue presents morphological regeneration and leads to the recovery of some functions of the spleen [3,6,8,10,12,21–32]. However, it is of fundamental importance to determine the amount of splenic tissue to be autotransplanted – critical mass – for the occurrence of functional regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…To that effect, of the 11 children tested, all were noted to have retained normal or near-normal serum levels of immunoglobulins G and M (IgG and IgM). Previous human and animal studies have shown that partial splenectomy leaving 20% to 30% of normal splenic volume does retain splenic immune function [7,13,14,[20][21][22][23]. Although some animal studies suggested isolated residual splenic tissue from the upper pole or from autotransplantation may not convey equivalent immunologic activity [21,22], other studies have found appropriate splenic morphology, viability, and stimulation of immune function with partial splenectomy supplied by gastric vessels [20,23,24].…”
Section: Splenic Functionmentioning
confidence: 99%
“…In der Literatur wurden jedoch nach Ligatur der A. lienalis in der Kindheit unauffĂ€llige Sonografien, Szintigrafien, Immunglobuline, Komplementfaktoren, Antikörpertiter nach Impfungen und sonstige Blutwerte beschrieben [36]. Tierexperimentell konnte gezeigt werden, dass nach partieller Milzresektion ein gewisser Schutz vor einer Pneumokokkeninfektion besteht [37,38]. Die phagozytĂ€re Funktion ist jedoch vermindert und korreliert mit dem Restgewicht [39,40].…”
unclassified